A Significant Pericardial Effusion Leading to Bronchial Compression: A Case Report - Suman Rao MD; Oluwateniola Olatunde MD; Akhila Sunkara MBBS; Vrinda Vyas MBBS; Andrew Weinberg DO (SAGE Publishing, 2021)
Commonly, pericardial effusions can cause suboptimal heart contractility. Larger pericardial effusions can lead to compression of structures that surround in the heart in the mediastinum. Our patient presented with dyspnea that required mechanical ventilation. Bronchoscopy revealed compression of the bronchus from an external source. Echocardiogram showed a large circumferential pericardial effusion, which compressed the left main stem bronchus causing left lung atelectasis and persistent respiratory failure. A subxiphoid pericardial window was performed, which led to an improvement in her oxygen requirements. This case portrays the importance of including pericardial effusions in patients who present with respiratory failure refractory to antibiotic treatment and intervention with bronchoscopy. Although our patient passed away, recognition and earlier appropriate management with a pericardial window or pericardiocentesis could have prevented this adverse event.